Processing ambiguities in attachment and pronominal reference. Issue 1 (28th July 2020) - Grant, Margaret; Sloggett, Shayne; Dillon, Brian
Abstract : The nature of ambiguity resolution has important implications for models of sentence processing in general. Studies of structural ambiguities, such as modifier attachment ambiguities, have generally supported a model in which a single analysis of ambiguous material is adopted without a cost to processing. Concurrently, a separate literature has observed a processing penalty for ambiguities in pronominal reference, suggesting that potential referents compete for selection during the processing of ambiguous pronouns. We argue that the apparent distinction between the ambiguity resolution mechanisms in attachment and pronominal reference ambiguities warrants further study. We present evidence from two experiments measuring eye movements during reading, showing that the separation held in the literature between these two ambiguity types is, at least, not uniformly supported.